2018
DOI: 10.1111/vsu.12787
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix scaffolds for treatment of large volume muscle injuries: A review

Abstract: The preponderance of current evidence supports the use of ECM for muscle defect repair only in specific instances, such as nonappendicular and/or partial-thickness defects. Consequently, clinical use of ECM in veterinary patients requires careful consideration of the specific ECM product, lesion size and location, and loading circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 123 publications
1
29
0
Order By: Relevance
“…While mice and rats are the most commonly utilized pre-clinical animal models because of the ease of conducting high throughput studies with standardized injury models, they typically create defects that are orders of magnitude smaller than those seen clinically. More recently, researchers have used larger preclinical animal models including dogs [138] and pigs [268], which generate defects on a more clinically relevant scale [269]. Additionally, muscles in varying anatomical locations have different functions, anatomy, and mechanical loading, which can influence regenerative outcomes [269].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mice and rats are the most commonly utilized pre-clinical animal models because of the ease of conducting high throughput studies with standardized injury models, they typically create defects that are orders of magnitude smaller than those seen clinically. More recently, researchers have used larger preclinical animal models including dogs [138] and pigs [268], which generate defects on a more clinically relevant scale [269]. Additionally, muscles in varying anatomical locations have different functions, anatomy, and mechanical loading, which can influence regenerative outcomes [269].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, researchers have used larger preclinical animal models including dogs [138] and pigs [268], which generate defects on a more clinically relevant scale [269]. Additionally, muscles in varying anatomical locations have different functions, anatomy, and mechanical loading, which can influence regenerative outcomes [269]. Musculoskeletal injury methods also vary and include myotoxic agents, hindlimb ischemia, and partial or total resection models.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of preclinical models of VML have been conducted in mice and rats [33]. However, a standard VML model with respect to muscle anatomical location and defect size has not been defined.…”
Section: Animal Models Of Vmlmentioning
confidence: 99%
“…However, a standard VML model with respect to muscle anatomical location and defect size has not been defined. The latissimus dorsi (LD), tibialis anterior (TA), quadriceps and abdominal wall muscles are the most frequently ablated muscles in experimentally induced VML [33]. Although in most VML models more than 20% of the muscle mass is ablated, Anderson et al reported that 15% muscle ablation was the critical threshold for irreversible muscle loss.…”
Section: Animal Models Of Vmlmentioning
confidence: 99%
“…Biomaterials are pivotal, as their interaction with the seeded cells will determine the final result of the tissue-engineered construct. For this aim, dealing with biologically derived materials seems to be a reasonable option, if the most relevant biochemical cues are preserved [ 9 , 15 , 16 ].…”
Section: Moving Towards Biomimetic Engineered Muscular Constructsmentioning
confidence: 99%